Statistical Considerations for Embedded Pragmatic Clinical Trials in People Living with Dementia. (26th June 2020) - Allore, Heather G.; Goldfeld, Keith S.; Gutman, Roee; Li, Fan; Monin, Joan K.; Taljaard, Monica; Travison, Thomas G.
Abstract : There is overwhelming need for nonpharmacological interventions to improve the health and well‐being of people living with dementia (PLWD). The National Institute on Aging Imbedded Pragmatic Alzheimer's Disease (AD) and AD‐Related Dementias Clinical Trials (IMPACT) Collaboratory supports clinical trials of such interventions embedded in healthcare systems. The embedded pragmatic clinical trial (ePCT) is ideally suited to testing the effectiveness of complex interventions in vulnerable populations at the point of care. These trials, however, are complex to conduct and interpret, and face challenges in efficiency (i.e., statistical power) and reproducibility. In addition, trials conducted among PLWD present specific statistical challenges, including difficulty in outcomes ascertainment from PLWD, necessitating reliance on reports by caregivers, and heterogeneity in measurements across different settings or populations. These and other challenges undercut the reliability of measurement, the feasibility of capturing outcomes using pragmatic designs, and the ability to validly estimate interventions' effectiveness in real‐world settings. To address these challenges, the IMPACT Collaboratory has convened a Design and Statistics Core, the goals of which are: to support the design and conduct of ePCTs directed toward PLWD and their caregivers; to develop guidance for conducting embedded trials in this population; and to educate quantitative and clinical scientists in the design, conduct, and analysis of these trials. In this article, we discuss some of the contemporary methodological challenges in this area and develop a set of research priorities the Design and Statistics Core will undertake to meet these goals. J Am Geriatr Soc 68:S68–S73, 2020 .